Peran Pemberian Mpasi Dini, Pengetahuan Ibu, dan Personal Hygiene dengan Kejadian Diare Pada Anak Usia 3 – 60 Bulan di Wilayah Kerja Puskesmas Narmada - Dewi, Ni Putu Ulan Sintya; Surasmaji, Lalu Irawan; Hidayati, Diani Sri; Wiatma, Deny Sutrisna (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Diarrhea is a cause of death in children under 5 years of age. Diarrhea is a potential Extraordinary Event (KLB) disease. Untreated diarrhea can cause dehydration and death. The high mortality rate due to diarrhea can be influenced by the provision of early complementary feeding, maternal knowledge, and personal hygiene. These risk factors can affect the child's digestive system and immunity because they are not yet fully formed. The aim was to determine the relationship between the provision of early complementary feeding, maternal knowledge, and personal hygiene with the incidence of diarrhea in children aged 3-60 months in the Narmada Health Center work area. Quantitative research with an observational approach using a cross-sectional design. The sampling technique used simple random sampling. The study was conducted in the Narmada Health Center work area, West Lombok in September 2024. The research sample was 84 respondents. The data obtained were analyzed using the Chi-square test with a significance value of p 0.05. The results of the bivariate analysis showed that there was a significant relationship between the provision of early MPASI and diarrhea with a p-value of 0.003, there was a significant relationship between maternal knowledge and diarrhea with a p-value of 0.004 and there was a significant relationship between personal hygiene and diarrhea with a p-value of 0.009. There was a significant relationship between the provision of early MPASI and the incidence of diarrhea, there was a significant relationship between maternal knowledge and the incidence of diarrhea, and there was a significant relationship between personal hygiene and the incidence of diarrhea in children aged 3-60 months in the Narmada Health Center work area. Keywords: Diarrhea, Early MPASI, Maternal Knowledge, Personal Hygiene  ABSTRAK Diare merupakan penyebab kematian pada anak kurang dari 5 tahun. Diare termasuk penyakit potensial Kejadian Luar Biasa (KLB). Diare yang tidak ditangani dapat menyebabkan dehidrasi hingga kematian. Tingginya angka kematian akibat diare dapat dipengaruhi oleh pemberian MPASI dini, pengetahuan ibu, dan personal hygiene. Faktor risiko tersebut dapat mempengaruhi sistem pencernaan dan imunitas anak karena belum terbentuk dengan sempurna. Tujuan untuk mengetahui hubungan pemberian MPASI dini, pengetahuan ibu, dan personal hygiene dengan kejadian diare pada anak usia  3 – 60 bulan di wilayah kerja Puskesmas Narmada. Penelitian kuantitatif dengan pendekatan observasional menggunakan desain cross sectional. Teknik pengambilan sampel menggunakan simple random sampling. Penelitian dilakukan di wilayah kerja Puskesmas Narmada, Lombok Barat pada bulan September 2024. Sampel penelitian sebanyak 84 responden. Data yang diperoleh dianalisis dengan uji Chi-square dengan nilai signifikasi p 0.05. Hasil analisis bivariat menunjukkan ada hubungan signifikan pemberian MPASI dini dengan diare dengan p-value 0,003, ada hubungan signifikan pengetahuan ibu dengan diare  dengan p-value 0,004  dan ada hubungan signifikan personal hygiee  dengan diare  dengan p-value 0,009. Terdapat hubungan signifikan pemberian MPASI dini dengan kejadian diare, terdapat hubungan signifikan pengetahuan ibu dengan kejadian diare, dan terdapat hubungan signifikan personal hygiene dengan kejadian diare  pada anak usia 3 – 60 bulan di wilayah kerja Puskesmas Narmada.  Kata Kunci: Diare, MPASI Dini, Pengetahuan Ibu, Personal Hygiene